Enhanced heat diffusion in nanofluid via DNA mediated aggregation. Issue 67 (29th June 2016) - John, Jisha; Thomas, Lincy; Kurian, Achamma; George, Sajan D.
Abstract : Thermal diffusivity increases with different shapes, concentration of gold nanoparticles and also with the addition of ssDNA while the addition of dsDNA found to be ineffective in causing any kind of change in the thermal diffusivity. Abstract : In this work, we have investigated the role of the type of DNA in the heat diffusion mechanism of single stranded DNA as well as double stranded DNA mixed with differently shaped green synthesized gold nanoparticle prepared via green synthesis route. We demonstrate that, irrespective of nanoparticle shape, heat diffusion, characterized by the effective thermal diffusivity value evaluated using a laser based dual beam thermal lens technique, increases not only with the concentration of nanoparticles but also with the addition of single stranded DNA. The addition of double stranded DNA found to be ineffective in causing any kind of change in the thermal diffusivity value for various concentrations of nanoparticles as well as DNA. The transmission electron microscopy image analysis of the mixture elucidates that single stranded DNA causing nanoparticle aggregation provides easy path of heat transport whereas no aggregation of gold nanoparticles are observed in the presence of double stranded DNA. Amongst the differently shaped (star, bean and spherical) nanoparticles of size ∼20 nm considered here, star shaped particles are found to aggregate more efficiently and result in maximum enhancement of the thermal diffusivity value, followed by bean and spherical shape. These results are further corroborated with the studies of thermal diffusivity evaluation of mixtures comprising of citrate stabilized negatively charged gold nanoparticle (∼5 nm)–DNA molecules. The UV-Vis absorption studies carried on the mixture also indicate the preferential aggregation of nanoparticles in the presence of single stranded DNA, as manifested as red shift in the plasmonic peak. An increase in the nanoparticle concentration as well as single stranded DNA concentration in the mixture indicates that the maximum enhancement occurs for the star shaped gold nanoparticles. The understanding of heat diffusion through DNA–gold nanoparticle may facilitate the development of biocompatible coolants or heat exchanges, DNA mediated assembly of nanoparticles etc.